Human Capital Management as an Indicator of Personnel Development in the International Company - Irina Yurievna EREMINA; Natalya Yurievna SOPILKO; Olga Yurievna MYASNIKOVA; Alena Vyacheslavovna CHUPROVA (Communications of International Proceedings, 2020)
The paper presents the results of research on improving the methodology of human capital management at enterprises, in particular, personnel efficiency increasing of international company of the oil and gas industry. The aim of the study is to find training methods for effective development of employees of the oil and gas industry for their labor productivity increasing. General scientific methods of analysis, logical generalization and comparison, as well as correlation analysis are used in the research. It is determined that human capital currently remains the most important competitive advantage in oil and gas companies’ market. The analysis showed that there are lots of existing methods used by companies for improving of their activity efficiency, but the methods of employees training and development deserve special attention. Within the framework of investigated enterprise, we have obtained the data which indicated that, despite the active use of various off-site methods of employees’ training, the company did not provide the economic feasibility of investing in personnel training. Developed complex workplace training methodology, based on coaching approach was introduced and tested and made it possible to obtain labor productivity indicator increasing. It is noted that such an approach is universal and in future it may contribute to strengthening in the relationship between labor productivity and training volume both for managers and workers of various categories of the other enterprises of oil and gas industry.
Keywords: Human Capital; Professional Education; Personnel Training; Coaching; Oil and Gas Companies